Cuba Inside Out : Revolution and Contemporary Theatre - Prizant, Yael (Book collections on Project MUSE., 2014)
The collapse of the Soviet Union in 1989 drastically altered life in Cuba. Theatre artists were faced with new economic and social realities that changed their day-to-day experiences and ways of looking at the world beyond the island. The Cuban Revolution's resistance to and intersections with globalization, modernity, emigration and privilege are central to the performances examined in this study. The first book-length study in English of Cuban and Cuban American plays, Cuba Inside Out provides a framework for understanding texts and performances that support, challenge, and transgress bounda.